VD_FINDINFO HC / 2011 / 581 vom 26. Oktober 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, CONJOINT, MODIFICATION DES CIRCONSTANCES, DIRECTIVEINJONCTION, DÉBITEUR | 132 al. 1 CC, 176 al. 1 ch. 1 CC, 179 CC